2000
DOI: 10.1096/fj.00-0399fje
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids control spasticity in a multiple sclerosis model

Abstract: Spasticity is a complicating sign in multiple sclerosis that also develops in a model of chronic relapsing experimental autoimmune encephalomyelitis (CREAE) in mice. In areas associated with nerve damage, increased levels of the endocannabinoids, anandamide (arachidonoylethanolamide, AEA) and 2-arachidonoyl glycerol (2-AG), and of the AEA congener, palmitoylethanolamide (PEA), were detected here, whereas comparable levels of these compounds were found in normal and non-spastic CREAE mice. While exogenously adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
290
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(318 citation statements)
references
References 32 publications
23
290
0
5
Order By: Relevance
“…Endocannabinoids, a novel class of lipid mediators, have been implicated in a growing number of neurological and psychiatric disorders, including schizophrenia, anxiety disorder, depression, Parkinson's disease, Alzheimer's disease, Huntington chorea and epilepsy, and have also been shown to have important neuroprotective effects in stroke and traumatic brain injury (reviewed in Pacher et al, 2006). Numerous studies have documented changes in the brain level of endocannabinoids in animal models for some of these diseases, such as Parkinson's (Di Marzo et al, 2000;Maccarrone et al, 2003), multiple sclerosis (Baker et al, 2001;Cabranes et al, 2005) or Huntington chorea (Bisogno et al, 2007), and in human brain tumors (Maccarrone et al, 2001). A tacit assumption in such studies is that the biochemical composition of the postmortem brain reliably reflects in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Endocannabinoids, a novel class of lipid mediators, have been implicated in a growing number of neurological and psychiatric disorders, including schizophrenia, anxiety disorder, depression, Parkinson's disease, Alzheimer's disease, Huntington chorea and epilepsy, and have also been shown to have important neuroprotective effects in stroke and traumatic brain injury (reviewed in Pacher et al, 2006). Numerous studies have documented changes in the brain level of endocannabinoids in animal models for some of these diseases, such as Parkinson's (Di Marzo et al, 2000;Maccarrone et al, 2003), multiple sclerosis (Baker et al, 2001;Cabranes et al, 2005) or Huntington chorea (Bisogno et al, 2007), and in human brain tumors (Maccarrone et al, 2001). A tacit assumption in such studies is that the biochemical composition of the postmortem brain reliably reflects in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al (2001) found that brains and spinal cords of spastic animals contained elevated levels of anandamide and 2-AG compared with control animals. Interestingly, exogenous administration of anandamide and 2-AG ameliorated spasticity within minutes (Baker et al, 2001). These results show that inflamed CNS tissues produce endocannabinoids and that augmenting this production may have a beneficial effect.…”
Section: Productionmentioning
confidence: 91%
“…Degradation Baker et al (2001) also used mice with EAE to examine the potential for pharmacologically targeting the FAAH enzyme as a treatment of neuroinflammation. A pharmacological inhibitor of FAAH, as well as inhibitors of the putative anandamide transporter, reduced spasticity within minutes, and effects were blocked by the administration of SR141716A in conjunction with SR144528 (Baker et al, 2001).…”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects observed here upon um-PEA administration can be due to PEA activating its molecular targets, and also to PEA favoring the actions of other NAEs (e.g., AEA and OEA). Indeed, anti-inflammatory, neuroprotective, and analgesic effects have been reported for AEA and OEA in several preclinical models [69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%